Correlación de lo valores de Hemoglobina, Hematocrito y Hierro Sérico con la calidad alimentaria en adultos mayores del Asilo de Ancianos del Cantón Yantzaza. - Pinzón Torres, Lorena Beatriz (2013)
The increased nutritional requirements in older adults is not covered by the usual diet, the same that has inadequate amounts of iron and have low bioavailability due to poor diet intake or the occurrence of diseases. As the state of optimal health and critical component is essential that older adults are more attention, since they face daily serious social and economic problems that influence nutritional status. The study aimed to quantify the values ​​of hemoglobin, hematocrit , iron and its relation to the consumption of foods rich in iron, so the research work was descriptive cross , we worked with 72 people from the Canton nursing Yantzaza that met the inclusion criteria , the analyzes were performed hemoglobin, hematocrit and serum iron by hand and colorimetric methods. Reached the following conclusions: That the hemoglobin and hematocrit values ​​were found decreased by 9.3 % of patients, whereas serum iron values ​​present diminished by 1.4 %. On the consumption of foods rich in iron, it was found that 85.71 % did not consume fish and 71.43 % do not eat meat, do not eat legumes and nuts consumed respectively. Likewise, the survey was identified by the most important factors for malnutrition are present: Problems with the teeth, poverty, gastrointestinal problems and poor consumption of foods rich in iron. Key words: hemoglobin, hematocrit, serum iron, food quality, Older Adults.